"If They Could Make Us Disappear, They Would!" Youth and Violence in Cite Soleil, Haiti - Willman, A. (2012)
This study explores community-level risk and protective factors for youth. violence in Cite Soled, Port-au-Prince's most violent slum. The youth of Cite Soleil have often been mobilized to violence by powerful actors as tools for achieving political or financial gain. Drawing on a formal survey (N = 1,575) and ethnographic data collected between March. 2008 and April 2009, we analyze the factors that contributed-and continue to contribute to making these youth available for such mobilization. Youth frame their experiences at terms of a broader social conflict between the "included" and the "excluded," and view violence as an effective means of obtaining what is denied to them by society: opportunity, respect, and material benefits. The experiences from Haiti offer important lessons in understanding the community level drivers of youth violence, and can contribute to policy approaches that go beyond stabilization, measures toward addressing structural violence. (C) 2010 Wiley Periodicals, Inc.